2007
DOI: 10.1186/1751-0759-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of juggling therapy on anxiety disorders in female patients

Abstract: AimsThe aim of this study was to investigate the effect of juggling therapy for anxiety disorder patients.Design and MethodSubjects were 17 female outpatients who met the DSM-IV diagnostic criteria for anxiety disorders. Subjects were treated with standard psychotherapy, medication and counseling for 6 months. For the last 3 months of treatment, subjects were randomized into either a non-juggling group (n = 9) or a juggling therapy group (juggling group: n = 8). The juggling group gradually acquired juggling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Continuing to juggle after the therapy may provide benefit in reducing ongoing anxiety, consistent with the results of Nakahara et al (2007), who found a reduction in trait anxiety from learning to juggle over a 6-month period. Some impediments to learning juggling are perfectionism, excessive task-outcome focus, and not allowing for a learning curve.…”
Section: Discussionsupporting
confidence: 81%
“…Continuing to juggle after the therapy may provide benefit in reducing ongoing anxiety, consistent with the results of Nakahara et al (2007), who found a reduction in trait anxiety from learning to juggle over a 6-month period. Some impediments to learning juggling are perfectionism, excessive task-outcome focus, and not allowing for a learning curve.…”
Section: Discussionsupporting
confidence: 81%
“…An additional strength of the J-BMLP may be that case study research has shown that juggling as a form of therapy also has a beneficial effect on treating refractory PTSD symptoms [ 51 ]. In addition, other studies have noted that regular juggling can also effectively reduce anxiety [ 52 ]. There is a suggestion that the temporal lobe of the brain is involved in generating panic attacks [ 53 ], so movement information and physical movement itself may be an important part of controlling this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Although this form of exercise seems demanding, research confirms that older people are fit enough to master juggling exercises [11,34]. One of the positive aspects of taking up this form of exercise is the growing evidence indicating that juggling improves the well-being of exercisers [34,[36][37][38]. In addition, our previous research showed that this form of exercise is attractive to older people [34].…”
Section: Introductionmentioning
confidence: 94%
“…Bonferroni post hoc analysis of RMS VX showed statistically significantly higher values for POST NJP versus the other time points (PRE JP -POST NJP: MD=-. 37 Participants were characterized by shorter response time between POST JP and the other time points, especially for SRT, VSRT, CRT, VCRT, DT and COG T . Additionally, changes in selected cognitive abilities in both conditions from PRE to POST measurements showed an advantage of JP (Fig.…”
Section: Primary Outcomesmentioning
confidence: 99%